Integrating Morphological and Molecular Techniques to Identify Intraspecific Crosses in Citrus - Manveen Kaur Batth; Anil Kumar Sangwan; Maninder Kaur (Archives of Current Research International, 2024)
The morphological analysis and simple sequence repeat molecular studies were conducted with the objective for the development of novel promising citrus rootstocks with resistance to phytophthora and salinity stress. This study was established as a novel citrus breeding program at Dr. J.C. Bakhshi Regional Research Station, Abohar, Punjab Agricultural University. Here, rough lemon (Citrus jambhiri) was used as female parent while trifoliate orange (Poncirus trifoliate), Carrizo (Carrizo citrange) and rangpur lime (Citrus limonia) were taken as the male parent. Rough lemon is productive, vigorous with high tolerance towards active lime and diseases viz. Citrus virus exocortis and Citrus tristeza virus, but it is susceptible to phytophthora pathogen. Trifoliate orange and carrizo, have been described as an “ultra-resistant rootstock” while rangpur lime is tolerant against salinity. Hybrids were derived from the cross between the C. jambhiri × P. trifoliate, C. jambhiri × C. citrange and C. jambhiri × C. limonia. The range of polymorphism information content (PIC) values ranged from 0.0 to 0.8 with 0.66 average PIC value. Seventy-three SSR markers were used for molecular analysis and the promising F50 marker showed maximum 0.87 PIC value that confirms the higher degree of polymorphism and diversity among the genotypes. The different combination of crosses undergo selection of 26 hybrid seedlings through both morphological and molecular screening utilizing Simple Sequence Repeats (SSR) markers. Thus, morphological and molecular approach proved to be effective for the differentiation of hybrids from nucellar seedlings among citrus rootstocks involving polyembryony cultivars.